(untitled) (Romanian Studies Today, 2024)
Max Blecher’s connections with the Central-European imagination, critically established through comparative readings of Franz Kafka and Bruno Schulz, could be revisited not only comparatively, but also by tackling some key issues in his work and biography that may confirm the writer’s belonging to this vast intellectual territory. Provincial spaces, marginality, uncertainties regarding identity, existential confusion, immaturity, the invasion of objects and the artificial, all reveal a perspective upon literature that may function, in the absence of geographical belonging, as a bridge and connection between worlds that mirror their essence and difference.